Biocatalytic Cascade Conversion of Racemic Epoxides to (S)‐2‐Arylpropionic Acids, (R)‐ and (S)‐2‐Arylpropyl Amines. Issue 1 (28th December 2022) - See, Willy W. L.; Li, Xirui; Li, Zhi
Abstract: New types of one‐pot multi‐step enzymatic cascade transformation involving dynamic kinetic resolution to convert racemic substrates to chiral products in high ee and yield were developed. Unique cascade reactions of easily accessible racemic trans ‐β‐methyl or α‐methyl epoxides to produce ( S )‐2‐arylpropionic acids, ( R )‐ and ( S )‐2‐arylpropyl amines were demonstrated via styrene oxide isomerase (SOI)‐catalyzed Meinwald epoxide rearrangement to generate 2‐arylpropanal in situ, which was followed by spontaneous racemization, and alcohol dehydrogenase (ADH)‐catalyzed ( S )‐enantioselective oxidation or transaminase (TA)‐catalyzed ( R )‐ or ( S )‐enantioselective amination, respectively. Cascade reactions performed with isolated enzymes or whole‐cell biocatalysts produced pharmaceutically relevant ( S )‐2‐arylpropionic acids, ( R )‐ and ( S )‐2‐arylpropyl amines with high enantioselectivity and yield. The cascades starting with in situ aldehyde generation from epoxides effectively minimized side reactions related to aldehyde instability and displayed a wide substrate scope. Abstract :